Tide gauge records show that the 18.61‐year nodal tidal cycle can change high water levels by up to 30 cm - Peng, Dongju (2019)
The lunar nodal cycle, produced by the varying declination of the Moon over a period of 18.61 years, drives changes in tidal amplitude globally. However, constraining the range of changes in tidal amplitude that can be expected over a nodal cycle from real observations is rarely considered for coastal hazard planning. In this study, we use hourly tide gauge observations with record lengths >19 years from 574 stations distributed worldwide to examine the contribution of the nodal modulation to monthly high water levels. Our results show that the influence of the lunar nodal cycle on high water levels is largest at tide gauge stations located in the Gulf of Tonkin, English Channel, and Bristol Channel, amounting up to 30 cm in range, suggesting that in the coming decades the impact of the nodal cycle on high water levels in those regions could be greater than that of global mean sea level rise, which is up to 17 cm by 2030, according to the Intergovernmental Panel on Climate Change fifth assessment report projections. We also examine the phase of nodal modulation and show that the estimated phases exhibit two clusters: one cluster (111° ± 10°) corresponds with the locations having a diurnal form of tides, whereas the other cluster (−59° ± 11°) corresponds with the locations exhibiting a semidiurnal form of tides. Nodal modulation in the diurnal and semidiurnal locations will peak again in 2025 and 2034, respectively, resulting in enhanced potential for coastal hazard in the respective regions.